A new model for the processes of droplet condensation and evaporation on solid surface. (September 2016) - Luo, Xisheng; Fan, Yu; Qin, Fenghua; Gui, Huaqiao; Liu, Jianguo
Highlights: Two regimes of mass and energy transfers are redefined and incorporated in our model. Empirical quantities are avoided because the model presents non-equilibrium process. This model is suitable for any droplet size and any surface size. Abstract: A new model is developed to describe quantitatively the processes of droplet condensation and evaporation on solid surface in the presence of non-condensable gas. By comparing the distance between vapor molecules and droplet surface with the mean free path of vapor–gas mixture, the environment outside droplet is divided into two regions with their own regimes of mass and energy transfers which are governed by kinetic theory and continuum flow theory, respectively. These two regimes are incorporated by matching the mass and energy fluxes from these two regions. The new model presents the non-equilibrium dynamic process of condensation and evaporation. In addition, the effects of solid surface on the droplet condensation and evaporation including the transfers of mass and heat are successfully considered which is suitable for any droplet size and any surface size (particle or flat). More parameters related to the condensation on solid surface can be obtained by the new model and, subsequently, empirical or fitting intermediate quantities are avoided. The critical degree of supercooling, the temperature of vapor–gas mixture at Knudsen layer interface, the variation rates of droplet radius are simulated by our model to prove that our model is credible. The results indicate that an approximate replacement of a homogeneous model in the simulation of droplet condensation and evaporation on solid surface is unsuitable.